7. SOME PHYSICAL AND PHYSIOLOGICAL CHARACTERISTICS IN MALE MILITARY MEDICAL STUDENTS AND CHANGES AFTER VESTIBULAR - COCHLEAR TEST (Vietnam Journal of Community Medicine, 2025)
Objective: To analyze some physical and physiological characteristics of circulation, respiration in male military medical students and changes of some indexs of circulation and respiratory system after performing vestibular - cochlear testing.Method: Cross-sectional descriptive study.Results: Most students have a balanced BMI (87.7%). Physiological indicators of circulatory, respiratory and vestibular functions of medical students mostly meet the requirements of future study and work. The percentage of students with satisfactory circulatory and respiratory functions is 88.7% and from 77.6% to 80.4%, respectively. The number of overweight students and those who do not meet the requirements in some strenuous activities need to increase physical activity, especially endurance training. 69.23% of students performed well in the vestibular - cochlear test, the physiological indicators changed with statistical significance: increased heart rate (p = 0.03), increased systolic blood pressure (p = 0.04) and decreased peripheral blood oxygen saturation (p = 0).Conclusion: Most male military medical students have physical condition and physiological function suitable for future learning and task requirements, however, it is still necessary to focus on improving physical strength and endurance in strenuous situations.
Keywords: Military medical students; physical; circulatory physiology; respiratory physiology, vestibular system function.